Population and development : high and low fertility in poorer countries - Hawthorn, Geoffrey (Routledge library editions. Development ;, 2011)
First published in 1978, this book explores the vital global issue of high and low fertility in poorer countries through a series of case studies by contemporary experts in the fields of development and demography. These studies examine such issues as: the relations between fertility rates and income distributions in poor societies; the question of whether or not neo-classical macro-economics are sufficient to understand and to try to engineer relations between economies and populations; and the specifics of the relations between fertility and a variety of socio-economic factors in both Sou.